Parametric estimation of ship maneuvering motion with integral sample structure for identification. (August 2015) - Jian, Cao; Jiayuan, Zhuang; Feng, Xu; Jianchuan, Yin; Zaojian, Zou; Hao, Yu; Tao, Xiao; Luchun, Yang
Highlights: Integral sample structure for identification is proposed for parametric identification of ship maneuvering motion. Least square support vector machines are employed as the system identification algorithm. Integral sample structure for identification is compared with Euler sample structure for identification. The superior of integral sample structure for identification is validated. Abstract: This documentation presents the parametric identification modeling of ship maneuvering motion with integral sample structure for identification (ISSI) and Euler sample structure for identification (ESSI) based on least square support vector machines (LS-SVM), where ISSI is used for the construction of in–out sample pairs. By using Mariner Class Vessel, the sample dataset are obtained from 15°/15° zigzag maneuvering simulation based on Abkowitz model. By analyzing the simulation data including rudder angle, surge velocity, sway velocity, yaw rate and so forth, the hydrodynamic derivatives in Abkowitz model are all identified. The validation of the proposed identification algorithm is verified by the high precisions of the identified hydrodynamic derivatives and maneuvering prediction results. The comparison is also conducted between the proposed ISSI and the conventional Euler sample structure for identification (ESSI), and the experimental results shows that ISSI is much more appropriate for parametric identification modeling of ship maneuvering motion.